Effect of Hydrokinesia in elderly subjects with Backward Disequilibrium - Chintamani, Radhika; Rayjade, Amrutkuvar; Yadav, Trupti (International Journal of Psychosocial Rehabilitation, 2020)
Background: Water based exercise are significant in improving both static as well as dynamic balance. Elderly subjects already are known to have decreased balance. Changes in the musculoskeletal system is one of the major cause of decreased balance. Physiotherapy regimen is important in improving both static and dynamic balance in elderly. Aquatic therapy is painless and easy way to improve balance in geriatric. However, Despite its widespread knowledge of importance of aquatic therapy in improvement of balance, the efficacy of aquatic therapy in elderly is limited. Purpose: The aim of this systematic review is to analyze the importance of aquatic therapy on fall perspective in elderly population. Methods: The authors searched Google Scholar and PubMed from 1996 to 2017. Only downloadable randomized controlled trials(15), randomized clinical trials(14) and experimental studies(3) were included in the study. Main results: The duration of treatment varied significantly in comparison to various studies. Subgroup analysis was performed on factors considered for measuring of fall risk parameters in elderly subjects. Conclusion: The result of the present study shows strong evidence to support the water based exercises in which Hydrokineitic therapy showed significant reduction in kinesiophobia and fall risk rate. Hence the therapy can be considered effective for geriatric population.